USING THE CHARACTER DOLL COSTUME TO FULFILL LIFE'S NEEDS - Widha Dhiyati (Universitas Lambung Mangkurat, 2021)
Phenomena or social phenomena are able to influence human attitudes and behavior in society. This study aims to reveal the general description of groups/buskers dressed as roadside character dolls and their intended use. The research method used is a qualitative method. The data sources were selected by purposive sampling. Data was collected by means of observation, interviews, and documentation. Analysis of research results using data reduction, display, and verification steps. The results of this study indicate that, The existence of the buskers dressed in character dolls is motivated by education, and age so they decide to become gamers on the side of the road. The use of character doll costumes aims to attract the sympathy of road users, the results of which are used to meet the necessities of life such as food/drink, shelter and education in order to survive. Based on the results of this study, it can be suggested for the local government to be able to open up employment opportunities and not support the existence of clown groups as a profession to earn a steady income and street clowns should also be given a place to study or be included in equivalency schools so that they can get a diploma and can apply for jobs. which is more suitable, for example being a security guard or cashier at Indomart or Alfamart and for clowns it is better to have other ways or other businesses to keep making money.